Distal enhancers upstream of the Charcot-Marie-Tooth type 1A disease gene PMP22 - Jones, Erin A. (Oxford University Press, 2012)
Myelin insulates axons in the peripheral nervous system to allow rapid propagation of action potentials, and proper myelination requires the precise regulation of genes encoding myelin proteins, including PMP22. The correct gene dosage of PMP22 is critical; a duplication of PMP22 is the most common cause of the peripheral neuropathy Charcot-Marie-Tooth Disease (CMT) (classified as type 1A), while a deletion of PMP22 leads to another peripheral neuropathy, hereditary neuropathy with liability to pressure palsies. Recently, duplications upstream of PMP22, but not containing the gene itself, were reported in patients with CMT1A like symptoms, suggesting that this region contains regulators of PMP22. Using chromatin immunoprecipitation analysis of two transcription factors known to upregulate PMP22—EGR2 and SOX10—we found several enhancers in this upstream region that contain open chromatin and direct reporter gene expression in tissue culture and in vivo in zebrafish. These studies provide a novel means to identify critical regulatory elements in genes that are required for myelination, and elucidate the functional significance of non-coding genomic rearrangements.